AFLES 2016 ENRICHES 170 ASEAN STUDENTS WITH LEADERSHIP CAPABILITIES AND NETWORKING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
NILAI, N. SEMBILAN, July 2016 – Some 170 university student leaders from the 10 ASEAN countries and Pakistan would participate in the 4th ASEAN Future Leaders Summit (AFLES) 2016 from 13 – 24 July 2016.